1977
DOI: 10.2134/agronj1977.00021962006900020006x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Corn Yield, Expressed as a Percentage of Maximum, and the N Percentage in the Grain. I. Various N‐rate Experiments1

Abstract: The objective of this investigation was to determine if the N content of the grain of corn (Zea mays L.) could be used as a measure of N sufficiency of the crop for maximum yield. This was done by studying the relationship between yield, expressed as a percentage of maximum, and the N percentage in the grain. The relationship was determined from the data of 13 site‐years of six N‐rate experiments in Iowa and from data reported in the literature. Two methods, a graphical and a regression method, were developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
38
3

Year Published

1982
1982
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 13 publications
8
38
3
Order By: Relevance
“…Annual N removal by the grain was estimated by adjusting the yield to zero g kg À1 water content and multiplying by the average 1992 grain N concentrations (12.9, 12.6, 12.2, and 11.3 (g N) kg À1 for moldboard plow, chisel plow, ridge-tillage, and no-tillage practices, respectively). Grain N concentrations were not measured during the other years, but the values for 1992 were within the range reported by Pierre et al (1977) for corn grown in N-rate studies throughout Iowa, USA.…”
Section: Production Practices N Applied and N In Harvested Grainsupporting
confidence: 72%
“…Annual N removal by the grain was estimated by adjusting the yield to zero g kg À1 water content and multiplying by the average 1992 grain N concentrations (12.9, 12.6, 12.2, and 11.3 (g N) kg À1 for moldboard plow, chisel plow, ridge-tillage, and no-tillage practices, respectively). Grain N concentrations were not measured during the other years, but the values for 1992 were within the range reported by Pierre et al (1977) for corn grown in N-rate studies throughout Iowa, USA.…”
Section: Production Practices N Applied and N In Harvested Grainsupporting
confidence: 72%
“…This is comparable to figures of 1.52 and 1.54% reported by Pierre et al (1977a). Insufficient trials were sampled in the Waikato to permit a valid comparison between seasons, but Pierre et al (1977a) suggested that moisture stress had little if any effect on the % N value between 70 and 100 % relative yield.…”
supporting
confidence: 75%
“…This is comparable to figures of 1.52 and 1.54% reported by Pierre et al (1977a). Insufficient trials were sampled in the Waikato to permit a valid comparison between seasons, but Pierre et al (1977a) suggested that moisture stress had little if any effect on the % N value between 70 and 100 % relative yield. Relative yield-percent N relationships for grain calculated from published results covering 15 hybrids and a range oflocations and plant populations showed that the % N associated with maximum yield ranged from 1.38 to 1.77 (mean 1.53) (Pierre et al 1977a).…”
supporting
confidence: 75%
“…(1 grain for wheat based on ratios of crop components to grain yield (Bolinder et al 2007b) and N concentrations derived from literature sources (Pierre et al 1977;Wichmann 1998;Canadian Fertilizer Institute 2001;Preston 2002 Available N was derived from organic N mineralization, atmospheric N deposition and N fertilizer application. Total deposition of atmospheric N was estimated as a proportion of total annual precipitation (0.025 kg N mm…”
Section: Description Of Modelmentioning
confidence: 99%